PROBLEMATIKA KETERAMPILAN MEMBACA DAN MENULIS PADA MAHASISWA PENDIDIKAN BAHASA INDONESIA UM-TAPSEL - Lili Herawati Parapat; Rahmat Huda (Jurnal Hata Poda, 2022)
This study aims to determine the causes of problems or problems that often arise in the world of education. In this case, the main cause is the lack of curiosity about reading, whether it is the purpose of reading, the benefits of reading, the important role of reading for oneself and the surrounding environment. The cause of problems in writing is not knowing where to start. Too many things that seem to be the same make it difficult for people to be interested. I don't have the right language. To imagine that everything is already known to everyone. The method used in this research is to collect accurate data through interviews, recording, and taking notes. The expected results in this study are to be able to solve the problems of low reading, increase interest in reading, foster creativity in reading, develop knowledge by reading, change consumptive thinking patterns by reading and writing.Keywords: problematic, reading, writing.